Tinjauan Hukum Islam Terhadap Organisasi Komunikasi Nasional Aksi Peduli Dalam Pembinaan Muallaf Menuju Keluarga Sakinah Pasca Perkawinan Di Kabupaten Boyolali - Rahmawati, Evi Dian; Syamsudin; Baehaqi (JOM, 2024)
This article aims to examine the role of the National Communication Organization for Caring Action (KNAP) in guiding converts towards establishing a harmonious family based on Islamic principles after marriage in Boyolali Regency. By reviewing Islamic jurisprudence, this study underscores the importance of religious guidance provided by KNAP to converts, particularly in instilling fundamental beliefs (aqidah) and practicing correct religious rituals. Employing a field research methodology, including observation, interviews, and documentation, data were collected and subsequently processed and analyzed. The findings reveal that KNAP plays a crucial role in delivering religious guidance to converts, addressing various post-marriage challenges. Moreover, KNAP's activities adhere to Islamic principles, encompassing educational initiatives for converts and solutions for field-related obstacles, supported by informative publications aimed at enhancing public comprehension. KNAP offers a physical platform for communication and coordination, conducts continuous studies to fortify faith, delivers social services, and collaborates with dawah activists to ensure comprehensive propagation efforts. The implication of this research lies in providing a deeper understanding of KNAP's contributions in guiding muallaf individuals towards establishing families grounded in Islamic values. Future research endeavors could delve further into the dynamics of fostering muallaf individuals and cultivating sakinah families within diverse social and cultural contexts.